Highly valued despite burdens: Qualitative implementation research on rapid tests for hospital-based SARS-CoV-2 screening - Jonas Wachinger; Shannon A. McMahon; Julia Lohmann; Manuela De Allegri; Claudia M. Denkinger (SSM: Qualitative Research in Health, 2022)
Antigen-based rapid diagnostic tests (RDTs) for SARS-CoV-2 have good reliability and have been repeatedly implemented as part of pandemic response policies, especially for screening in high-risk settings (e.g., hospitals and care homes) where fast recognition of an infection is essential. However, evidence from actual implementation efforts and associated experiences is lacking.We conducted a qualitative study at a large tertiary care hospital in Germany to identify step-by-step processes when implementing RDTs for the screening of incoming patients, as well as stakeholders’ implementation experiences. We relied on 30 in-depth interviews with hospital staff (members of the regulatory body, department heads, staff working on the wards, staff training providers on how to perform RDTs, and providers performing RDTs as part of the screening) and patients being screened with RDTs.Despite some initial reservations, RDTs were rapidly accepted and adopted as the best available tool for accessible and reliable screening. Decentralized implementation efforts resulted in different procedures being operationalized across departments. Procedures were continuously refined based on initial experiences (e.g., infrastructural or scheduling constraints), pandemic dynamics (growing infection rates), and changing regulations (e.g., screening of all external personnel). To reduce interdepartmental tension, stakeholders recommended high-level, consistently communicated and enforced regulations.Despite challenges, RDT-based screening for all incoming patients was observed to be feasible and acceptable among implementers and patients, and merits continued consideration in the context of high infection and stagnating vaccination rates.